2011
DOI: 10.1088/0953-8984/23/34/346003
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal excitations in quantum antiferromagnets

Abstract: By extending our recently proposed magnon-density waves to low dimensions, we investigate, using a microscopic many-body approach, the longitudinal excitations of the quasi-one-dimensional (quasi-1d) and quasi-2d Heisenberg antiferromagnetic systems on a bipartite lattice with a general spin quantum number. We obtain the full energy spectrum of the longitudinal mode as a function of the coupling constants in the original lattice Hamiltonian and find that it always has a nonzero energy gap if the ground state h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
11
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 45 publications
6
11
1
Order By: Relevance
“…Our preliminary calculation for the two dimensional triangular model [25] have been extended to the quasi-1D Hexagonal structures of CsNiCl 3 and RbNiCl 3 , where we find that our numerical results for the energy gap values at the magnetic wavevector are in good agreement with experimental results after inclusion of the high-order contributions in the large-s expansion [26]. In this article, we extend similar high-order calculations to the bipartite antiferromagnetic systems where the long-ranged order is collinear [27].…”
Section: Introductionsupporting
confidence: 70%
See 2 more Smart Citations
“…Our preliminary calculation for the two dimensional triangular model [25] have been extended to the quasi-1D Hexagonal structures of CsNiCl 3 and RbNiCl 3 , where we find that our numerical results for the energy gap values at the magnetic wavevector are in good agreement with experimental results after inclusion of the high-order contributions in the large-s expansion [26]. In this article, we extend similar high-order calculations to the bipartite antiferromagnetic systems where the long-ranged order is collinear [27].…”
Section: Introductionsupporting
confidence: 70%
“…For the longitudinal mode, we have examined the behaviors of in N (q) and S(q) in the isotropic limit (A → 1) in our earlier paper [27] and found that both have the same divergence asg 1…”
Section: A Results For Linear Chain (1d) Modelmentioning
confidence: 96%
See 1 more Smart Citation
“…In analogy to Feynmann's theory of the low-lying excited states in the helium-4 superfluid [25,26], we identify the longitudinal excitation states in a quantum antiferromagnet with a Néel-like order as the collective modes of the magnon-density waves. In application to the quasi-1D tetragonal structure of KCuF 3 with s = 1/2, with no other fitting parameters than the nearest-neighbor coupling constants in the model Hamiltonian, we find that our numerical results for the energy gap values at the magnetic wavevector are in general agreement with the experiments [27]. We hope that more experimental results for the energy spectra at other wavevectors will be available for comparison.…”
Section: Introductionsupporting
confidence: 68%
“…The logarithmic behavior of the structure factor and the energy spectrum of the triangular lattice model is similar to that of the square lattice model investigated earlier [39,42,46,47]. We have identified these gapless modes of the 2D models as quasi-gapped modes because any finite size effect or anisotropy will induce a large energy gap when compared with the counterparts of the spin-wave spectrum.…”
Section: Magnon-density Waves In 2d Triangular Latticesupporting
confidence: 73%